PENGARUH PROFITABILITAS, LIKUIDITAS, SOLVABILITAS DAN EARNING PER SHARE TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR BEI PERIODE 2020-2022 - Ningsih, Diah Wuriah (Dinamika Akuntansi Keuangan dan Perbankan, 2024)
his study aims to analyze the influence of Profitability, Liquidity, Solvency, and Earnings Per Share on the Going Concern Audit Opinion in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The sample was selected using the purposive sampling method, resulting in 135 data points. The findings indicate that profitability has a significant negative effect on the going concern audit opinion. Liquidity is shown to affect the going concern audit opinion. Solvency also influences the going concern audit opinion. Furthermore, Earnings Per Share impacts the going concern audit opinion. Collectively, Profitability, Liquidity, Solvency, and Earnings Per Share are found to influence the going concern audit opinion.